Trator rosa da Valtra: do marketing social à representatividade da mulher no agro - (:unkn) unknown (Universidade Federal do Pampa, 2024)
This research addresses concepts of marketing, social marketing, breast cancer, and Pink October and female representation. This work analyzed Valtra's Pink Tractor campaign, aiming to understand the connection between how social marketing was used to promote awareness about breast cancer prevention, while at the same time becoming a symbol of female empowerment and representation in the agricultural sector. Valtra is a tractor brand that arrived in Brazil in 1960, and is a company in the agricultural sector, a sector predominantly dominated by men. The approach and general objective of this work seek to understand how the pink tractor became a symbol of social marketing and representation for women in agriculture. One of the main methodologies used was a bibliographic review, which included authors such as Rudio (1992), Santaella (2001), Kotler (1993), Vaz (1995), Aaker (2003 and 2015), and Philip Kotler and Kevin Lane Keller (1993) to support reflections on communication strategies and the social impacts of marketing campaigns in the agro-industrial context. To complement this theoretical basis, an exploratory study was conducted, the nature of which allows the investigation of topics that have not yet been addressed or that require a more detailed initial understanding. Descriptive analysis was used to organize and interpret the data systematically, with the aim of understanding the specific characteristics of the campaign. Finally, the non-participant observation technique was adopted, a method that allows the recording and analysis of the interactions and repercussions of the campaign without the direct interference of the researcher. The main results obtained through the analysis of the publications meet the initial objective by pointing out that the posts analyzed showed the broad repercussion of the campaign, with favorable comments and involvement, demonstrating the effect of the supported cause.
Keywords: Marketing Social; Mulheres na agricultura; Mamas – Câncer – Campanhas; Valtra (Empresa de tratotres); Agricultura; Social Marketing; Women in agriculture; CNPQ::CIENCIAS SOCIAIS APLICADAS